EVALUASI PELAKSANAAN KURIKULUM 2013 DAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) PADA PEMBELAJARAN GEOGRAFI DI SMAN KOTA PADANG - Maijem Simponi; M Iqbal Liayong Pratama (JAMBURA GEO EDUCATION JOURNAL, 2020)
Education system has it's own problems.  Indonesia's education also involves the challenge of implementing the new curriculum. The schools are not ready yet to implement the new curriculum, the 2013 curriculum. The 2013 curriculum which emphasizes character development, requires teachers to carry out comprehensive learning and a full assessment of each student's development. This study aims to describe and evaluate the implementation of the 2013 Curriculum and SBC in geography learning at High School in Padang city. This research used descriptive qualitative by using purposive sampling. The sample of this paper are teachers and students who teach and learn geographic subject, principals and vice-principals.  The Data were collected through observation, interviews and documentation.  The results revealed that:  (1) Evaluation of the implementation of KTSP; The planning of learning in SBC emphasizes more on the delivery of material whose learning success is measured through cognitive tests. The implementation of KTSP learning is carried out conventionally, depending on the teacher and creative learning. Teachers' creativity in teaching is the main in creating creative learning so that national education goals are achieved. Assessment of KTSP learning uses reference criteria; that is based on what students understand after participating in the learning process, using a test gauge. Learning success can be seen in the acquisition of student learning outcomes. (2)evaluation of the 2013 curriculum, planning is designed based on instructions from the government and must explore all the potentials and abilities of students and all norms of life. The implementation of 2013 curriculum learning, learning is carried out holistically to achieve overall objectives as well, so that all potential students will be explored listed in the four core competencies by using various assessment instruments, Assessment in  the 2013 curriculum is carried out based on scientific assessments that assess all potentials possessed by participant. Assessment is not only limited to the test instrument, but also through various instruments